SISTEM INFORMASI PAKET PERNIKAHAN BERBASIS WEB PADA RIZI CATERING DENGAN PHP DAN MySQL - Sepitri Daruyani; Orita Dwi Purbiyanti; Irawaty, Irawaty,; Ahmad Rayhan (Jurnal Manajamen Informatika Jayakarta, 2026)
A wedding package promotion website is a solution to make it easier for prospective customers to obtain service information quickly and accurately. This study aims to build a wedding package marketing website for Rizi Catering that provides complete information about service packages, a documentation gallery, and an order form that is directly connected to WhatsApp marketing. The development method used is the Waterfall model, which includes the following stages: analysis, design, implementation, testing, and maintenance. The website was developed using PHP for system logic, MySQL as the database, and CSS for the user interface. Testing results using the Black Box Testing method showed that all functions operate as designed, pages load properly, the booking form successfully saves data to the database, and WhatsApp integration functions optimally. Additionally, the User Acceptance Test (UAT) results achieved an average percentage of 77%, indicating that the Rizi Catering website is well-received by visitors. The research findings can be accessed via https://rizicatering.free.nf/. Thus, the website successfully fulfills the research objectives as an informative promotional tool while simplifying the initial order documentation process at Rizi Catering.